An introduction to risk management - Shaw, Gregory (Henry Stewart Talks, 2015)
The terms risk and risk management have multiple definitions, Risk is a function of scenarios, their probabilities and consequences, Risk is generally marked by unknowns and uncertainties, Proven methods are available to bound risk uncertainties, Risk management is a process including identification, assessment and analysis for identifying options for treating risks, Risk management options include risk avoiding, ignoring, transferring, and/or mitigating, Effective risk management requires realistic objectives and recognition of boundary conditions, Open, honest, and audience specific communication supports risk management, A risk-informed approach applies risk information along with other relevant considerations and inputs to decision making